Pengaruh Lingkungan Sosial dan Potensi Diri Terhadap Minat Melanjutkan Studi Ke Perguruan Tinggi Pada Siswa Kelas XII SMA Pembangunan Laboratorium UNP - Dilla Suryani; Armiati Armiati (Universitas Negeri Padang, 2022)
This study aims to determine: 1) The influence of the social environment and self-potential on the interest in continuing their studies to college in class XII students of SMA UNP Laboratory Development; 2) The influence of the social environment on the interest in continuing their studies to college in class XII Laboratory Development. UNP High School; 3) The effect of self-potential on the interest in continuing their studies to higher education in grade XII students of UNP High School Laboratory Development. This research is a quantitative research with associative type. The population of this research is the XII grade students of SMA UNP Laboratory Development. The sampling method was determined by the Proportional Random Sampling technique and the sample used was 132 people. Data collection techniques using a questionnaire. This study uses multiple linear regression data analysis which includes F test (simultaneous), determinant coefficient (R2), and t test. The results of this study indicate that the social environment and self-potential have a positive and significant effect on the interest in continuing their studies to college in class XII students of SMA UNP Laboratory Development.